(untitled) (Journal of the College of Basic Education, 2024)
The research aimed to identify the effect of the Needham model on the acquisition of physical concepts and cognitive motivation among female students in the fourth science grade. The researcher adopted an experimental design with partial control for two equal groups with a post-test. The research sample consisted of (51) female students from the fourth science grade in middle school ( Zaha Hadid for girls). With (25) female students for the experimental group, and (26) female students for the control group, parity was conducted between the two research groups in variables (chronological age calculated in months, general average in the third middle school, previous information test, cognitive motivation scale), and among the requirements of the research is the preparation of teaching plans. Based on the Needham model and the usual method, the researcher prepared a test for the acquisition of physical concepts, consisting of 27 multiple-choice items, as a measurement tool to measure the first dependent variable, which is (the acquisition of physical concepts), and based on the researcher’s measure of cognitive motivation that he prepared (Saleh, 2012), after verifying Its psychometric properties, as a tool for measuring the second dependent variable, which is (cognitive motivation). After the end of the experiment, the researcher applied the two research tools to the two research groups. The data was collated and treated statistically. The results showed the significant impact of the Needham constructivist model on both the acquisition of physical concepts and cognitive motivation, and in light of Results: The researcher presented a number of recommendations and proposals.